The influence of work-family conflict, job stress, and organizational commitment on the turnover intention of female employees - Jayantara, I Ketut Adi; Sukarnasih, Desak Made (Review of Management, Accounting, and Business Studies, 2022)
This study aimed to identify the influence of work-family conflict, job stress, and organizational commitment on the turnover intention of woman employees at Pusat Oleh-Oleh Agung Bali Tanah Lot Tabanan. It was a quantitative study that showed and explained the influence of work-family conflict, job stress, and organizational commitment on the turnover intention of woman employees at Pusat Oleh-Oleh Agung Bali Tanah Lot Tabanan. The population of this study was the women employees of Pusat Oleh-Oleh Agung Bali Tanah Lot Tabanan. There were 50 respondents the woman employees who work at Pusat Oleh-Oleh Agung Bali Tanah Lot Tabanan as the samples of this study. The technique of sampling by using saturated samples was used. The instrument was examined by validity and reliability tests. The data were analyzed by multiple linear regression, classic assumption test, determination coefficient, test T, and test F. The result of the study showed that (1) work-family conflict has a positive and significant impact on the turnover intention of woman employees with a significance score of 0.001, (2) job stress has a positive and significant impact on the turnover intention of women employees with the significance score 0.029, (3) organization commitment has a negative and significant impact on the turnover intention of woman employees with the significance score 0.035, (4) work-family conflict, job stress, and organization commitment give simultaneous impact on turnover intention of woman employees at Pusat Oleh-Oleh Agung Bali Tanah Lot Tabanan.